Smart kote glove for assessment of scoring parameters of dan and kyu grade kendokas - Jeong, K.; Tan, A. M.; Fuss, F. K. (Proceedings, 2018)
Kendo is one of the most ancient swordsmanship arts in Japan. The aims of this study are to develop and test an innovative smart Kote glove for assisting the Kendoka to distinguish scoring from non-scoring Kote (wrist) strikes. An in-house developed pressure sensing platform was utilized to develop the smart Kote glove. Ten kendo practitioners, comprising of five Dan (black belts equivalent) and five Kyu (lower level/ungraded of both genders), participated in this study. The results showed significant differences between Dan and Kyu participants in both accuracy and sharpness of the strikes. Dan grade participants showed higher percentage of hitting the target comparing to Kyu grade (92% and 75% respectively). The percentage of scoring was also significantly higher in Dan (78%) than in Kyu (37%) grades. The average impact force of scoring by Dan grade (1159 ± 379 N) was higher than by Kyu grade (852 ± 429 N).